Curriculum Development Management at Madrasah Aliyah Negeri - Annisa Addina Pohan; Fachruddin Azmi; Tien Rafida (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
This study aims to determine how the management of curriculum development in MAN Padang Lawas Utara. This research used a qualitative approach with a descriptive type. Data collection techniques used observation, interviews and documentation techniques to obtain valid data about curriculum development management at MAN Padang Lawas Utara. Based on the results of the study, it shows that 1) The planning of curriculum development at MAN Padang Lawas Utara is quite good, which includes: the background of the preparation of curriculum development based on the needs and feasibility of the madrasah, reviewing the vision, mission and goals of education, formulation of curriculum content, projects that need to be done, design strategies in learning, design guidance strategies in dealing with problems, design assessment strategies to determine the level of success that has been achieved after implementing curriculum development, 2) Organizing curriculum development management at MAN Padang Lawas Utara is quite good, because it is carried out regularly and planned. Conducted by a curriculum development team formed by the principal. So that it makes it easier to make curriculum and get effective and efficient results, 3) The implementation of curriculum development at MAN Padang Lawas Utara is going well, according to the agenda that has been prepared by the curriculum development team, namely determining the curriculum structure to support competency standards, 4) Evaluation of development North Padang Lawas MAN curriculum is quite good, it can be seen with monitoring and assessment to determine the implementation of curriculum development by the principal and the supervisory team. Supervision is carried out starting from planning, organizing to implementing curriculum development internally and externally. as teacher professional education training (TPT), as well as collaboration between teachers and students.